2008
DOI: 10.1682/jrrd.2007.09.0138
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of PTSD Checklist in sample of male veterans

Abstract: Abstract-The psychometric properties of the PTSD Checklist (PCL) were investigated in a sample of treatment-seeking and community-dwelling male veterans. In conjunction with previous reports, results from the present study indicate that the PCL possesses strong, robust psychometric properties. The current investigation suggests a cutoff score of 60-higher than previous investigations-related to posttraumatic stress disorder (PTSD) diagnosis derived from the Clinician-Administered PTSD Scale. This research supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(212 citation statements)
references
References 19 publications
4
206
1
1
Order By: Relevance
“…Recommended cut points have ranged from 31 [19] to 60 [20], and there remains lack of consensus regarding the best diagnostic threshold for the PCL-C [21][22]. The minimum possible score that corresponds with a Diagnostic and Statistical Manual of Mental Disorders-IV [23] diagnosis of PTSD is 41 and is thus considered clinically significant [17].…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Recommended cut points have ranged from 31 [19] to 60 [20], and there remains lack of consensus regarding the best diagnostic threshold for the PCL-C [21][22]. The minimum possible score that corresponds with a Diagnostic and Statistical Manual of Mental Disorders-IV [23] diagnosis of PTSD is 41 and is thus considered clinically significant [17].…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…It is one of the most widely used self-report instruments for assessing PTSD [23][24]. Published accounts of PTSD screening for both civilian and military versions of the PCL, with variations in populations, settings, reference standards, research methods, and optimality criteria, have reported optimal cutoff scores ranging from 28 to 60 [22,[25][26][27][28][29][30][31][32][33][34][35][36][37]. Each patient was given the PCL during consultation, with an opportunity to complete in a self-reported manner so that we could gain a raw score measure of PTSD symptom severity.…”
Section: Source Of Datamentioning
confidence: 99%
“…The PCL has revealed strong connections with other PTSD symptom questionnaires -i.e. correlations with the Mississippi Combat Related PTSD r = .93, Impact of Events Questionnaire r = .90 [4] and Clinician-Administered PTSD Scale r = .79 [10]. In comparison to afflicted individuals, individuals without PTSD reported significantly lower mean scale scores [3] and scale scores were sensitive to treatment [11].…”
Section: Introductionmentioning
confidence: 99%